2018
DOI: 10.1007/s42438-018-0007-6
|View full text |Cite
|
Sign up to set email alerts
|

Digital Immortality and Virtual Humans

Abstract: The use of virtual assistants such as Siri that provide voice and conversational interfaces, the growth of machine learning techniques to mine large data sets and the rise in the level of autonomy being given to computer-controlled systems all represent shifts in artificial intelligence that are enhancing the creation of digital immortality. The growth of personality capture and levels of brain simulation as well as computationally inspired life after death may change the future of religion, affect understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 20 publications
0
23
0
3
Order By: Relevance
“…This might lead to the intentional or accidental recreation of the deceased and facilitate the transmission of automated messages from the dead to the living (Bassett, 2015;Gibson, 2015). Some scholars (Meese et al, 2015;Savin-Baden & Burden, 2018;Sofka et al, 2017) have identified several services available in the digital age that harness the digital persona of the dead into thanatechnologies, such as Eter9, an SNS that allows users to create a digital version of themselves (a 'Counterpart') that learns about each user through his/her interaction in the SNS (Eter9, 2017); Lifenaut, which orients users to create detailed data about themselves to be incorporated into advanced software (LifeNaut Project, 2017); and Eternime, which mines data from other SNS and tries to replicate an individual's personality in an algorithm that users later train through daily interactions (Eterni.me., 2019). These thanatechnological services fulfil 'a dual role in helping someone achieve digital immortality and to cope with impending death and grief' (Sofka et al, 2017, p. 181).…”
Section: The Intersubjective Construction Of Personhood and The Digital Persona Of The Deadmentioning
confidence: 99%
See 2 more Smart Citations
“…This might lead to the intentional or accidental recreation of the deceased and facilitate the transmission of automated messages from the dead to the living (Bassett, 2015;Gibson, 2015). Some scholars (Meese et al, 2015;Savin-Baden & Burden, 2018;Sofka et al, 2017) have identified several services available in the digital age that harness the digital persona of the dead into thanatechnologies, such as Eter9, an SNS that allows users to create a digital version of themselves (a 'Counterpart') that learns about each user through his/her interaction in the SNS (Eter9, 2017); Lifenaut, which orients users to create detailed data about themselves to be incorporated into advanced software (LifeNaut Project, 2017); and Eternime, which mines data from other SNS and tries to replicate an individual's personality in an algorithm that users later train through daily interactions (Eterni.me., 2019). These thanatechnological services fulfil 'a dual role in helping someone achieve digital immortality and to cope with impending death and grief' (Sofka et al, 2017, p. 181).…”
Section: The Intersubjective Construction Of Personhood and The Digital Persona Of The Deadmentioning
confidence: 99%
“…In this sense, it is similar to Martine Rothblatt's (2014) concept of the 'mindclone', with the key difference that the VDP assumes a limited version of cyberconsciousness: it would be able to accurately display, but not experience, emotions, and despite being able to provide insights on numerous issues based on original 'equations' (similar to thoughts), it would lack subjective, phenomenal processes such as internal self-narratives. The VDP concept emerges from considering the possibilities afforded by the current and envisioned development of Virtual Humans (Burden & Savin-Baden, 2019), Paramortals (Onufrijchuk, 2016), Thanabots (Bassett, 2018) and Digital Immortals (Savin-Baden & Burden, 2018). The VDP and other digital immortality concepts seen in Table 1, as well as the phenomena they describe, are indicative of the beginning stages of a postmortal society where symbolic forms of immortality are being sought and digital technologies promise to realise them.…”
Section: The Virtual Deceased Person (Vdp): a Form Of Digital Immortality In Late Modernitymentioning
confidence: 99%
See 1 more Smart Citation
“…Religion also plays a role in our attitudes toward intelligent devices: a large number of studies claim that relying on Judeo‐Christian traditions may allow people to co‐exist with virtual reality entities (avatars, uploaded human consciousness in an online space, and so on) than coping with physically embodied devices such, among others, as robots, whereas people from, for example, the Shinto tradition find robots useful and pleasant to coexist with (Geraci 2006; Lee and Sabanovic 2014). Other scholars pay attention to the question of immortality (Rougier 2016; Savin‐Baden and Burden 2019): how virtual reality may be the awaited heaven on earth and the impact of this on our ethical and moral beliefs.…”
Section: Death Randomness Determinism and Probabilitymentioning
confidence: 99%
“…The digital 2 generation was formed under the influence of information-communication, computer and digital technologies, determining the character of socialization of their representatives, specificity of their value orientations, network identity and sociocultural image. Following the trends of the information society, the educational system in Russia has changed a lot, for example, some new models and theories of education appear, including tutoring, involving the use of mobile devices to maintain contact with tutors through apps like Whatsapp or Facebook; joint online education; learning through play, group projects [5]. In the course of education, they interact with Internet technologies, advanced software, which let them create the Internet products of their own, acquire and digest large amounts of information in short time.…”
Section: The Phenomenon Of Inculturation In the Modern Educational Enmentioning
confidence: 99%